(untitled) (World Bulletin of Public Health, 2024)
Today, there is an increase in the number of children with acute respiratory diseases. In 25–31% of children, respiratory infections occur with the clinical picture of obstructive bronchitis, and in 30–50% of cases it takes a protracted, undulating or recurrent course. Obstructive bronchitis in children attracts close attention from pediatricians due to their prevalence, lack of clear diagnostic criteria and difficulty of therapy. This study will determine the clinical and immunological characteristics of young children with obstructive bronchitis